1996
DOI: 10.1152/ajpendo.1996.270.4.e614
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin and IGF-I in activation of muscle protein synthesis after oral feeding

Abstract: The aim was to evaluate the role of insulin and insulin-like growth factor I (IGF-I) in activation of muscle protein synthesis after oral feeding. Synthesis rate of globular and myofibrillar proteins in muscle tissue was quantified by a flooding dose of radioactive phenylalanine. Muscle tissue expression of IGF-I mRNA was measured. Normal (C57 Bl) and diabetic mice (type I and type II) were subjected to an overnight fast (18 h) with subsequent refeeding procedures for 3 h with either oral chow intake or provis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
64
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 21 publications
6
64
0
Order By: Relevance
“…Concomitantly, the association of 4E with 4E-BP1 increases with starvation and diminishes with refeeding whereas the association of 4E with 4G, as expected responds in the reciprocal manner (20). As regards the relative importance of insulin versus nutrients in the control of 4E-BP1 phosphorylation, it is notable that the changes in phosphorylation of 4E-BP in response to fasting and feeding remain intact in NOD and ob/ob mice (20), diabetic models who fail to show any change in insulin concentration in response to these dietary maneuvers (2).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Concomitantly, the association of 4E with 4E-BP1 increases with starvation and diminishes with refeeding whereas the association of 4E with 4G, as expected responds in the reciprocal manner (20). As regards the relative importance of insulin versus nutrients in the control of 4E-BP1 phosphorylation, it is notable that the changes in phosphorylation of 4E-BP in response to fasting and feeding remain intact in NOD and ob/ob mice (20), diabetic models who fail to show any change in insulin concentration in response to these dietary maneuvers (2).…”
mentioning
confidence: 66%
“…At least three sets of independently regulated site-specific p70 phosphorylations have been identified; one is a set of Ser/Thr-Pro motifs clustered in a psuedosubstrate autoinhibitory domain in the noncatalytic carboxyl-terminal tail (Ser-434, -441, and -447; Thr-444 in p70␣1) 2 (45,48). A second site is Thr-412, 2 located in a unique hydrophobic segment; homologous sites of regulatory phosphorylation have been identified in PKCs and c-Akt/ PKB (45).…”
Section: Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that hyperaminoacidemia stimulates amino acid transport and net MPS, unlike carbohydrate administration both in the young [173] and in the elderly [174]. The effects on protein synthesis arise independently of changes in anabolic hormone concentration [175,176], although insulin is required for the effects of EAA on translation [177]. Among EAA, Branched chain amino acids (BCAA: leucine, isoleucine and valine) play a very important role as nutrient signals that regulates MPS through the stimulation of insulin-independent and rapamycin-sensitive pathways [178,179].…”
Section: Essential Amino Acidsmentioning
confidence: 99%
“…Feeding induces a rapid increase in the synthesis rate of total proteins in the skeletal muscle (1)(2)(3)(4) and liver (1,4) of growing postabsorptive animals. The signals responsible for stimulating protein synthesis remain unclear, though several studies have suggested a media tory role for amino acids in this anabolic response (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%